High-quality organic-inorganic hybrid perovskite material and preparation method thereof
By incorporating Co2+ and H2NCHNH2+ ions into the perovskite material, high-quality (CH3NH3)1-a(H2NCHNH2)aPb1-bCobX3 material is formed, which solves the problem of easy decomposition of perovskite materials in specific environments, and significantly improves the stability of the material and the performance of optoelectronic devices.
Patent Information
- Application Number
- CN202411915266.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Existing perovskite materials are easy to decompose under water vapor, oxygen, ultraviolet light, high temperature and other environments, resulting in poor stability of optoelectronic devices, limiting their commercial applications.
By incorporating Co2+ and H2NCHNH2+ ions into the perovskite material, a high-quality (CH3NH3)1-a(H2NCHNH2)aPb1-bCobX3 material is formed, and the lattice is enhanced by using Co2+ ions, and the H2NCHNH2+ ions suppress lattice distortion and reduce intrinsic defects and grain boundary defects.
It effectively improves the stability of perovskite materials, reduces the intrinsic defects and grain boundary defects of Pb vacancy and X vacancy, and improves the optical performance of the material and the long life of the device.
Smart Images

Figure CN119707706A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor materials, and in particular relates to a high-quality organic-inorganic hybrid perovskite material and a preparation method thereof. Background Art
[0002] Organic-inorganic hybrid perovskite (abbreviated as perovskite, its molecular formula is ABX3, where A is CH3NH3 + 、H2NCHNH2 + , Cs + etc., B is Pb 2+ Sn 2+ etc., X is Cl - Br - ,I - ) is a direct bandgap semiconductor material with high optical absorption coefficient (>10 4 cm -1 ), long carrier lifetime (>1.0μs), long carrier diffusion length (>1.0μm) and can be prepared in low-temperature solutions. It is an important semiconductor material for the preparation of low-cost and high-performance optoelectronic devices such as solar cells, photodetectors and light-emitting diodes. However, perovskite optoelectronic devices have the problem of poor stability, which seriously hinders their commercial application. In essence, the easy decomposition and ion migration of perovskite materials in environments such as water vapor, oxygen, ultraviolet light, and high temperature are the main reasons for the poor stability of perovskite optoelectronic devices. The use of physical isolation and heat dissipation technology can reduce the influence of water vapor, oxygen and high temperature factors, while light-induced decomposition and ion migration are inherent properties of perovskite materials, which are closely related to the intrinsic defects and grain boundary defects of perovskite materials. It is generally believed that only by preparing high-quality and low-defect perovskite materials can the problem of poor stability of perovskite materials and devices be fundamentally solved. Therefore, the design and preparation of high-quality perovskite materials are of great significance to the development and promotion of the commercial application of perovskite optoelectronic devices. Summary of the invention
[0003] In view of some deficiencies of existing perovskite materials, the present invention provides a high-quality organic-inorganic hybrid perovskite material and a preparation method thereof.
[0004] The molecular formula of the high-quality organic-inorganic hybrid perovskite material is (CH3NH3) 1-a (H2NCHNH2) a Pb 1- b Co b X3, wherein X is one or more combinations of Cl, Br or I, and the values of a and b are both positive numbers less than 1.
[0005] The method for preparing the high-quality organic-inorganic hybrid perovskite material comprises the following steps:
[0006] Step 1: Prepare CH3NH3X / PbX2 precursor solution:
[0007] Mix CH3NH3X and PbX2 materials and dissolve them in a mixed solution of dimethylformamide and dimethyl sulfoxide, and stir them thoroughly to form a CH3NH3X / PbX2 precursor solution;
[0008] Step 2: Configure Co 2+ Salt precursor solution:
[0009] A certain amount of CoX2, ZIF-67 or cobalt acetate is dissolved in the CH3NH3X / PbX2 precursor solution obtained in step 1, and stirred and allowed to stand in turn to form Co 2+ Co with ion concentration of 0.01~0.10mol / L 2+ Salt precursor solution;
[0010] Step 3: Prepare the perovskite spin coating solution:
[0011] Dissolve a certain amount of H2NCHNH2X material in the Co 2+ The salt precursor solution is stirred thoroughly and allowed to stand to form a perovskite spin coating solution with a H2NCHNH2X concentration of 0.02 to 0.20 mol / L;
[0012] Step 4, pre-treating the substrate;
[0013] Step 5: Spin-coat the perovskite spin-coating solution of step 3 on the substrate pretreated in step 4 by using a one-step spin-coating method of anti-solvent crystallization; after the spin-coating, perform a thermal annealing treatment: first anneal at 70-85°C for 1-10 minutes, and then anneal at 90-180°C for 9-30 minutes; obtain (CH3NH3) 1-a (H2NCHNH2) a Pb 1-b Co b X3, wherein X is one or more combinations of Cl, Br or I, a is the molar ratio of H2NCHNH2 in the total amount of CH3NH3 and H2NCHNH2 in the perovskite spin-coating solution, and b is the molar ratio of Co in the total amount of Co and Pb in the perovskite spin-coating solution.
[0014] Preferably, in step 1, the molar ratio of CH3NH3X and PbX2 materials is 0.9:1 to 1.1:1, and the concentrations of CH3NH3X and PbX2 are both 0.2 to 1.4 mol / L.
[0015] Preferably, in step 1, the volume ratio of dimethylformamide to dimethyl sulfoxide is 4:1 to 9:1.
[0016] Preferably, in step 4, the substrate is ITO glass or FTO glass.
[0017] Preferably, in step 4, the pretreatment steps of the substrate include:
[0018] Step A1: Ultrasonically clean the substrate successively with acetone, ethanol, and deionized water for 4 - 15 minutes to remove impurities and oil on the surface of the substrate;
[0019] Step A2: Blow dry the water droplets on the surface of the substrate with nitrogen;
[0020] Step A3: Place the substrate in an oven to further dry the remaining water droplets on the surface of the substrate;
[0021] Step A4: Place the substrate in an oxygen plasma machine or an ozone cleaning machine and clean for 10 - 20 minutes to enhance the hydrophilicity of the substrate surface.
[0022] Preferably, in step 5, the anti-solvent is one or a combination of ethyl acetate, toluene, and chlorobenzene.
[0023] Use of the organic-inorganic hybrid perovskite material prepared by the present invention for preparing perovskite optoelectronic devices.
[0024] The beneficial effects of the present invention are:
[0025] In the perovskite CH3NH3PbX3 material of the present invention, Co 2+ and H2NCHNH2 + ions are incorporated to form a high-quality (CH3NH3) 1-a (H2NCHNH2) a Pb 1-b Co b X3 (0 < a < 1, 0 < b < 1) perovskite material. In this material, Co 2+ ions occupy the B lattice site of the perovskite structure, enhancing the perovskite lattice and effectively reducing the intrinsic defects and grain boundary defects of Pb vacancies and X vacancies in the perovskite material; H2NCHNH2 + ions occupy the A lattice site of the perovskite structure, inhibiting the lattice distortion caused by the doped Co 2+ ions and effectively reducing the formation of Co 2+ ion interstitial defects. Description of the Drawings
[0026] Figure 1 is (CH3NH3) 1-a (H2NCHNH2) a Pb1-b Co b Schematic diagram of the preparation process of X3 perovskite material (DMF and DMSO in the figure are dimethylformamide and dimethyl sulfoxide respectively); a-preparation process of perovskite spin coating solution, b-perovskite (CH3NH3) 1-a (H2NCHNH2) a Pb 1-b Co b Spin coating process of X3 film;
[0027] Figure 2 Yes (CH3NH3) 1-a (H2NCHNH2) a Pb 1-b Co b Schematic diagram of the structure of X3 perovskite material;
[0028] Figure 3 Yes (CH3NH3) 0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 Photo of the I3 perovskite material;
[0029] Figure 4 Yes (CH3NH3) 0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 SEM images of I3 perovskite materials; a-surface, b-cross section;
[0030] Figure 5 is (CH3NH3)Pb 0.99 Co 0.01 I3 and (CH3NH3) 0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 XRD results of I3 perovskite material. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] (CH3NH3) 1-a (H2NCHNH2) a Pb 1-b Co b The preparation process of X3 perovskite material is as follows Figure 1 As shown, the structure is Figure 2 As shown;
[0033] Embodiment 1:
[0034] (1) Pretreatment of ITO glass substrate;
[0035] Take an ITO glass with a size of 15 mm × 15 mm;
[0036] The ITO glass was ultrasonically cleaned for 5 minutes using acetone, ethanol, and deionized water in sequence to remove impurities and oil stains on the surface of the ITO glass;
[0037] Use a nitrogen gun to blow dry the water droplets on the surface of the ITO glass;
[0038] Use an oven (temperature 60°C) to dry the residual water droplets on the ITO glass surface;
[0039] Clean the ITO glass with an oxygen plasma machine for 15 minutes to increase the hydrophilicity of the ITO glass surface;
[0040] (2) Prepare CH3NH3I / PbI2 precursor solution. Mix CH3NH3I and PbI2 materials in a molar ratio of 1:1 and dissolve them in a mixed solution of dimethylformamide and dimethyl sulfoxide (the volume ratio of the two is 4:1), stir, and obtain a 1.3 mol / L CH3NH3I / PbI2 precursor solution;
[0041] (3) The ZIF-67 material was dissolved in the CH3NH3I / PbI2 precursor solution, stirred at room temperature for 12 hours, and then allowed to stand at room temperature for 6 hours to obtain a ZIF-67 concentration of 3.0 mg / mL Co 2+ Salt precursor solution;
[0042] (4) Dissolve H2NCHNH2I material in Co 2+ The salt precursor solution was stirred at room temperature and allowed to stand to obtain a perovskite spin coating solution with a H2NCHNH2I concentration of 4.6 mg / mL;
[0043] (5) 80 μL of the perovskite spin coating liquid was evenly dropped onto the pretreated ITO substrate for spin coating. The spin coating parameters were: a rotation speed of 5000 r / min, a spin coating time of 30 s, and 400 μL of ethyl acetate was added at the 8th second of the spin coating to obtain a perovskite liquid film;
[0044] (6) The perovskite liquid film was placed on a hot plate and annealed at 70°C for 1 minute and 100°C for 10 minutes to obtain (CH3NH3) 0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 I3 perovskite thin film materials;
[0045] Figure 2 Shows (CH3NH3)0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 Schematic diagram of the structure of I3 perovskite material, it can be seen that Co occupies the Pb lattice site and H2NCHNH2 occupies the center of the perovskite cube;
[0046] Figure 3 Shows (CH3NH3) 0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 The photo of the I3 perovskite film shows that it is dark black, uniform in color, and highly absorbent;
[0047] Figure 4 Shows (CH3NH3) 0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 The surface and cross-sectional SEM images of the I3 perovskite thin film material show that the surface is dense, without holes, with large grain size and uniform thickness;
[0048] Figure 5 shows (CH3NH3)Pb 0.99 Co 0.01 I3 and (CH3NH3) 0.98 (H2NCHNH2) 0.02 Pb 0.99 Co 0.01 The XRD curve of I3 perovskite thin film material shows that H2NCHNH2 + The ions did not change the crystal structure of the perovskite material and eased the incorporation of Co 2+ Ion-induced compressive strain.
[0049] Embodiment 2:
[0050] (1) Pretreatment of ITO glass substrate;
[0051] Take an ITO glass with a size of 15 mm × 15 mm;
[0052] The ITO glass was ultrasonically cleaned for 5 minutes using acetone, ethanol, and deionized water in sequence to remove impurities and oil stains on the surface of the ITO glass;
[0053] Use a nitrogen gun to blow dry the water droplets on the surface of the ITO glass;
[0054] Use an oven (temperature 60°C) to dry the residual water droplets on the ITO glass surface;
[0055] Clean the ITO glass with an oxygen plasma machine for 15 minutes to increase the hydrophilicity of the ITO glass surface;
[0056] (2) Prepare CH3NH3I / PbI2 precursor solution. Mix CH3NH3I and PbI2 materials in a molar ratio of 1:1 and dissolve them in a mixed solution of dimethylformamide and dimethyl sulfoxide (the volume ratio of the two is 4:1), stir, and obtain a 1.3 mol / L CH3NH3I / PbI2 precursor solution;
[0057] (3) The ZIF-67 material was dissolved in the CH3NH3I / PbI2 precursor solution, stirred at room temperature for 12 hours, and then allowed to stand at room temperature for 6 hours to obtain a ZIF-67 concentration of 6.0 mg / mL Co 2+ Salt precursor solution;
[0058] (4) Dissolve H2NCHNH2I material in Co 2+ The salt precursor solution was stirred at room temperature and allowed to stand to obtain a perovskite spin coating solution with a H2NCHNH2I concentration of 9.2 mg / mL;
[0059] (5) 80 μL of the perovskite spin coating liquid was evenly dropped onto the pretreated ITO substrate for spin coating. The spin coating parameters were: a rotation speed of 5000 r / min, a spin coating time of 30 s, and 400 μL of ethyl acetate was added at the 8th second of the spin coating to obtain a perovskite liquid film;
[0060] (6) The perovskite liquid film was placed on a hot plate and annealed at 70°C for 1 minute and 100°C for 10 minutes to obtain (CH3NH3) 0.96 (H2NCHNH2) 0.04 Pb 0.98 Co 0.02 I3 perovskite thin film materials;
[0061] Embodiment 3:
[0062] (1) Pretreatment of ITO glass substrate;
[0063] Take an ITO glass with a size of 15 mm × 15 mm;
[0064] The ITO glass was ultrasonically cleaned for 5 minutes using acetone, ethanol, and deionized water in sequence to remove impurities and oil stains on the surface of the ITO glass;
[0065] Use a nitrogen gun to blow dry the water droplets on the surface of the ITO glass;
[0066] Use an oven (temperature 60°C) to dry the residual water droplets on the ITO glass surface;
[0067] Use a UV ozone machine to clean the ITO glass for 20 minutes to increase the hydrophilicity of the ITO glass surface;
[0068] (2) Prepare CH3NH3Br / PbBr2 precursor solution. Mix CH3NH3Br and PbBr2 materials in a molar ratio of 1.05:1 and dissolve them in a mixed solution of dimethylformamide and dimethyl sulfoxide (the volume ratio of the two is 8:1), stir, and obtain a 0.4 mol / L CH3NH3Br / PbBr2 precursor solution;
[0069] (3) The ZIF-67 material was dissolved in the CH3NH3Br / PbBr2 precursor solution, stirred at room temperature for 12 hours, and then allowed to stand at room temperature for 6 hours to obtain a ZIF-67 concentration of 1.39 mg / mL Co 2+ Salt precursor solution;
[0070] (4) Dissolve H2NCHNH2Br material in Co 2+ The salt precursor solution was stirred thoroughly at room temperature and allowed to stand to obtain a perovskite spin coating solution with a H2NCHNH2Br concentration of 1.5 mg / mL;
[0071] (5) 80 μL of the perovskite spin coating liquid was dropped onto the ITO, and a perovskite film was prepared by spin coating. The spin coating parameters were as follows: the first stage speed was 500 r / min, the spin coating time was 5 s, the second stage speed was 3000 r / min, the spin coating time was 20 s, and 300 μL of a toluene / ethyl acetate mixed solution (the volume ratio of the two was 1:2) was dropped at 8 seconds of the second stage spin coating to obtain a perovskite liquid film;
[0072] (6) The perovskite liquid film was placed on a hot plate and annealed at 80°C for 1 minute and 120°C for 15 minutes to obtain (CH3NH3) 0.97 (H2NCHNH2) 0.03 Pb 0.985 Co 0.015 Br3 perovskite thin film materials.
[0073] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A high-quality organic-inorganic hybrid perovskite material, characterized in that: The molecular formula is (CH3NH3) 1-a (H2NCHNH2) a Pb 1-b Co b X3, wherein X is one or more combinations of Cl, Br and I, and the values of a and b are both positive numbers less than 1.
2. The method for preparing high-quality organic-inorganic hybrid perovskite material according to claim 1, characterized in that: The steps include: Step 1: Prepare CH3NH3X / PbX2 precursor solution: Mix CH3NH3X and PbX2 materials and dissolve them in a mixed solution of dimethylformamide and dimethyl sulfoxide, and stir them thoroughly to form a CH3NH3X / PbX2 precursor solution; Step 2: Configure Co 2+ Salt precursor solution: One or more of CoX2, ZIF-67 or cobalt acetate is dissolved in the CH3NH3X / PbX2 precursor solution obtained in step 1, and stirred and allowed to stand in sequence to form Co 2+ Co with ion concentration of 0.01~0.10mol / L 2+ Salt precursor solution; Step 3: Prepare the perovskite spin coating solution: Dissolve the H2NCHNH2X material in the Co 2+ The salt precursor solution is stirred thoroughly and allowed to stand to form a perovskite spin coating solution with a H2NCHNH2X concentration of 0.02 to 0.20 mol / L; Step 4, pre-treating the substrate; Step 5: Spin-coat the perovskite spin-coating solution of step 3 on the substrate pretreated in step 4 by using a one-step spin-coating method of anti-solvent crystallization; after the spin-coating, perform a thermal annealing treatment: first anneal at 70-85°C for 1-10 minutes, and then anneal at 90-180°C for 9-30 minutes; obtain (CH3NH3) 1-a (H2NCHNH2) a Pb 1-b Co b X3, Wherein, X is one or more combinations of Cl, Br or I, a is the molar ratio of H2NCHNH2 in the total amount of CH3NH3 and H2NCHNH2 in the perovskite spin-coating solution, and b is the molar ratio of Co in the total amount of Co and Pb in the perovskite spin-coating solution.
3. The preparation method according to claim 2, characterized in that: In step 1, the molar ratio of CH3NH3X and PbX2 materials is 0.9:1 to 1.1:1, and the concentrations of CH3NH3X and PbX2 are both 0.2 to 1.4 mol / L.
4. The preparation method according to claim 2, characterized in that: In step 1, the volume ratio of dimethylformamide to dimethyl sulfoxide is 4:1 to 9:
1.
5. The preparation method according to claim 2, characterized in that: In step 4, the substrate is ITO glass or FTO glass.
6. The preparation method according to claim 2, characterized in that: In step 4, the pretreatment step of the substrate includes the following steps: Step A1, ultrasonically clean the substrate using acetone, ethanol, and deionized water in sequence for 4-15 minutes to remove impurities and oil stains on the surface of the substrate; Step A2, drying the water droplets on the surface of the substrate with nitrogen; Step A3, placing the substrate in an oven to further dry the remaining water droplets on the surface of the substrate; Step A4: Place the substrate in an oxygen plasma machine or an ozone cleaning machine for cleaning for 10 to 20 minutes to enhance the hydrophilicity of the substrate surface.
7. The preparation method according to claim 2, characterized in that: In step 5, the antisolvent is one or more combinations of ethyl acetate, toluene and chlorobenzene.
8. Use of the organic-inorganic hybrid perovskite material according to claim 1 for preparing a perovskite photoelectric device.
Citation Information
Patent Citations
Organic-inorganic hybrid perovskite semiconductor material and preparation method thereof
CN107591486A
Perovskite film defect passivation method
CN116546865A
Perovskite thin film, perovskite solar cell and preparation method thereof
CN118019359A